A sociological and biological study of human-wildlife interactions - Taylor, Emily (My University, 2018)
Urbanisation transforms habitat for wild animals and increases their interaction with humans as they compete for space and resources. Encounters between humans and wildlife in the City of Johannesburg Municipality (COJ) often end in conflict, more so with species that may be feared or disliked. To improve the nature of interactions between wildlife and people, it is important to understand where wildlife occurs, what kinds of conflicts it is involved in and where, and people’s common motivations for how they engage with wildlife. This study aimed to provide a biological and a sociological investigation into the nature and causes of human-wildlife conflict in the City of Johannesburg. I conducted analyses of wildlife sightings reports from a number of different sources, to develop a better understanding of the distribution of wildlife in the municipality, and to determine whether locations of reports were influenced by factors such as land-cover class, proximity to green spaces, or human population density. I conducted similar analyses on reports of human-wildlife conflict incidents to determine whether reported incidents were influenced by the aforementioned factors, as well as by the number of presence records for these locations. I also intended to determine what common types of conflict occurred and where. Spatial analysis of available presence and conflict data suggested that both wildlife presence and conflict incidents were more commonly reported in regions in which certain land-cover classes, such as residential areas with dense trees, are prevalent, and within 1 km of green spaces. To investigate potential underlying socio-demographic influences of human behaviour towards urban wildlife, I conducted surveys of 416 adolescents from three schools in different areas of Johannesburg, and 779 adult urban residents. The surveys were adapted from existing scales and designed to ascertain levels of basic knowledge about wildlife, general attitudes towards wildlife, the types of behaviour respondents are likely to show when encountering wildlife, and ultimately to reveal relationships between these measures. I found that respondents’ attitudes towards wildlife were significantly influenced by the extent of their knowledge, however knowledge was shown to have developed as a result of more than just formal education received. I also found that predicted behaviour towards wildlife was predominantly affected by both knowledge levels and attitudes. Demographic variables such as age and gender did influence all three measures but culture was the most significant demographic predictor of knowledge, attitude, and behaviour. These findings provide an indication that human-wildlife interactions can be effectively improved through developing people’s knowledge. However this must be addressed through both formal education and informal cultural teachings to have significant impact, particularly for interactions with animals that have deeply ingrained negative cultural associations, such as owls and bats.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Science
Keywords: Habitat (Ecology); Human-animal relationships; Wildlife conservation--Social aspects